Flat rate taxicabs and the production of urban space in depression-era Madison, Wisconsin. (January 2021) - Epstein, Seth
Abstract: The Great Depression prompted a reconsideration of value in urban space. This occurred in the taxi industry when flat rates supplanted metered rates. The arrival of low fare flat rate taxis in Madison, Wisconsin in 1932 quickly led to a threefold increase in the number of cabs and the nearly complete cessation of cabs' use of taximeters. Similar developments occurred elsewhere in U.S. cities during the 1930s. Earning the same fee for trips that varied in length and distance disrupted the homogeneity and abstraction of space and time which meters provided. The low fare flat rate system held out the promise of affordable transportation to passengers and economic self-sufficiency to drivers. However, despite its standardized rate, the space produced by participants in this system was characterized by unpredictability and uncertainty, as drivers sought to maximize their number of trips while minimizing the distance and duration of each trip. The uncertainty generated by these efforts, the lower capital costs associated with the flat rate system, and a rise in customer demand led to a significant increase in taxicabs traveling city streets, which in turn made it more difficult for drivers to make a living. By examining the production of space engendered by the low fare flat rate system, this article demonstrates how the pressures of the Depression deepened the contradictions of capitalist political economy. Highlights: Examines the flat rate taxicab system in Great Depression-era Madison, Wisconsin. Argues that the Depression prompted a reconsideration of value in urban space. Demonstrates that populist sentiment protected flat-rate cabs' operation. Shows how the flat-rate system depended on uncertainty for customers and drivers. Argues this uncertainty shows Depression-influenced tensions in capitalism.